RANCANG BANGUN SEPEDA PORTABLE CHARGING STATION 12V 6W - Alif Nurrachman Aji Saputra; Indra Riyanto (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
In this final project, a portable charging station bicycle is designed using a generator to produce electrical energy that comes from mechanical energy. This final project aims to determine whether the MPPT system commonly used in solar cells can also work on a different system, namely using a generator (bicycle dynamo). This tool gets input in the form of mechanical energy from pedaling a bicycle that rotates the bicycle wheel and causes the generator to also rotate. The system designed is a generator connected to a bicycle wheel, a rectifier circuit, a DC-DC converter, PWM, and a microcontroller. The discussion of the problem is focused on making renewable energy using mechanical energy through a generator whose voltage will be controlled using the Maximum Power Point Tracking (MPPT) method. Based on the system designed, the output of the generator when the bicycle is not ridden has an average power range of 4-6 Watt, after pairing it with MPPT it has an average power range of 5-6 Watt. Meanwhile, when the bicycle is ridden with an additional load the rider has an average power range of 4-6 Watt, after pairing it with MPPT it has an average power range of 3-6 Watt. The charging system that has been made can charge the battery, but it is not very effective. This is because the capacity of the larger battery is used to turn on the charging system itself.